Can and Should Happiness Be a Policy Goal?. (October 2014) - Oishi, Shigehiro; Diener, Ed
This article summarizes policy-relevant happiness research and demonstrates that self-reported happiness could be used to evaluate public policies. Self-reported well-being (e.g., life satisfaction, happiness) tracks objective societal and economic conditions fairly well (e.g., the financial crisis of 2008) and helps quantify people's suffering (e.g., severe disability is roughly twice as aversive as unemployment). Evidence also demonstrates that some liberal policies, such as generous unemployment benefits, progressive taxation, and income equality, are positively associated with citizens' self-reported well-being, whereas others (e.g., larger governmental spending per Gross Domestic Product [GDP]) are not. Just as the regular recording of economic activities helps gauge the effectiveness of specific policies and the general economic well-being of individuals and society at large, the regular recording of citizens' self-reported well-being will help gauge the effectiveness of specific policies, as well as the psychological well-being of individuals and society at large.